2009 Asia-Pacific Power and Energy Engineering Conference 2009
DOI: 10.1109/appeec.2009.4918683
|View full text |Cite
|
Sign up to set email alerts
|

Research on Dynamic Properties of Long Pipeline Monitoring System of Air Cushion Surge Chamber

Abstract: Air cushion Surge Chamber (ACSC) is a new type of pressure reduction device with some unique advantages like protecting the surface of the natural environment in hydropower plants. However, the inner air pressure of the ACSC could be as high as more than 3MPa, the monitoring system requires high accuracy and reliability to keep it working safely. In this paper, according to model test and numerical simulation, the dynamic response of the far distance monitoring system of ACSC with "long measuring pipelines" ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In the paper, it is shown that the mass and momentum balances for air inside the ACST can be further simplified with an ideal gas relation. Other studies include the gas seepage theory for air loss through the ACST chamber in [18], a monitoring method for the hydraulic behavior of the ACST in [19], stability analysis of the ACST in [20], etc. The model developed in most of the previous work assumes an adiabatic process for the cushioning of air inside the ACST.…”
Section: Previous Work and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the paper, it is shown that the mass and momentum balances for air inside the ACST can be further simplified with an ideal gas relation. Other studies include the gas seepage theory for air loss through the ACST chamber in [18], a monitoring method for the hydraulic behavior of the ACST in [19], stability analysis of the ACST in [20], etc. The model developed in most of the previous work assumes an adiabatic process for the cushioning of air inside the ACST.…”
Section: Previous Work and Contributionsmentioning
confidence: 99%
“…The air friction force F D,a modeled using Darcy's friction factor f D inside the ACST of Torpa HPP is considered using Equation ( 12) for the case of water level h ≤ H t , and using Equation (19) for the case of water level h > H t . The input to the turbine with valve signal u v for the simulation purpose is given by u v = 0.5 0 < t ≤ 500 s 0.95 500 s < t ≤ 1500 s where the hydro-turbine is loaded from half-load to nominal load at time t = 500 s. Figure 6 shows hydraulic behavior of the ACST for the turbine loading from 50% to 95%.…”
Section: Effect Of Air Friction Inside Acstmentioning
confidence: 99%
“…Dhakal [7] obtained the optimal size of the two-chamber surge chamber by taking the volume and throttle hole of the two-chamber surge chamber as the optimization variables, the surge extreme value and amplitude attenuation rate of the two-chamber surge chamber as the objective function using the non-dominated sorting genetic algorithm NSGA-II algorithm. Ou et al [8] proposed a type of semi-closed ACST body design combining the advantages of open and ACST. Simulation results show that the semi-closed air cushion surge chamber has simple structure and has the advantages of both the hydraulic performance of the surge tank in the transient process of large fluctuations and the rapid convergence of indoor water level in the transition process of small fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…C.Q. Qu et al [4] explained that every control modes have corresponding monitoring systems. PV/T control mode monitors pressure, volume and temperature.…”
Section: Introductionmentioning
confidence: 99%